National Geographic FieldScope: a platform for community geography. Issue 6 (1st August 2012) - Switzer, Anna; Schwille, Kathleen; Russell, Eric; Edelson, Daniel
Abstract : National Geographic FieldScope is designed to allow citizen scientists to visualize and analyze their data via online GIS maps. It is being developed with and for citizen‐science organizations and will facilitate collaborative problem solving and decision making.